The dynamics of decay processes in rare plasma - Antonov, A.N.; Buts, V.A.; Koval’chuk, I.K.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G.; Tarasov, D.V. (Вопросы атомной науки и техники, 2009)
The results of the experimental and theoretical investigations of chaotic decay process of HF wave on two new − HF and LF wave in the cylindrical resonator filled with rare plasma are presented. The branches of oscillations which can participate in such process are specified. The possible mechanisms of appearance of burst of radiation which follows after certain time delay after the main impulse obtained in the experiment are discussed. The qualitative agreement of the theoretical deductions with the experimental results is observed. Представлен результати експериментального та теоретичного дослідження процесу хаотичного розпаду ВЧ- хвилі на дві нові – ВЧ та НЧ в циліндричному резонаторі, що заповнений рідкою плазмою. Вказані гілки коливань, які можуть брати участь в такому процесі. Обговорюються можливі механізми появи виявленого в експерименті сплеску випромінювання, що з’являється з деякою часовою затримкою після першого імпульсу. Відзначено якісний збіг теоретичних висновків з експериментальними результатами. Представлены результаты экспериментального и теоретического исследования процесса хаотического распада ВЧ- волны на две новые – ВЧ и НЧ в цилиндрическом резонаторе, заполненном редкой плазмой. Указаны ветви колебаний, которые могут участвовать в таком процессе. Обсуждаются возможные механизмы появления обнаруженного в эксперименте всплеска излучения, следующего с некоторой временной задержкой после основного импульса. Отмечено качественное согласие теоретических выводов с экспериментальными результатами.